TECHNOLOGY OF E-GOVERNMENT ACCEPTANCE ANALYSIS ON ELECTRONIC RESIDENT IDENTIFICATION CARD (E-KTP) ADOPTION - Agustina Dias Kartikasari; Jaryono Jaryono; Daryono Daryono (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2016)
The aim of this study is to analyze the effects of Technology Readiness Index (TRI) toward Technology Perceptions that will determine the Actual Usage of e-KTP adoption by taking of 50 people which is the all the population as the respondents. This study investigates the relationship between the personality dimensions of TRI (Technology Readiness Index) and the system specific dimensions of TAM (Technology Acceptance Model). Multiple regressions was used to test the relationship between the dimensions of TRI and TAM. The results show that Optimism influence perceived usefulness and perceived ease of use. Innovativeness and Discomfort influence perceived ease of use. Further, perceived usefulness and perceived ease of use has a significant positive influence on actual usage.